Inactivation of Dermatophytes Causing Onychomycosis Using Non-Thermal Plasma as a Prerequisite for Therapy - Lokajová, Eliška; Julák, Jaroslav; Khun, Josef; Soušková, Hana; Dobiáš, Radim; Lux, Jaroslav; Scholtz, Vladimír (Journal of fungi (Basel, Switzerland), 2021)
Following our previous study of the therapy of onychomycosis by non-thermal plasma (NTP) and nail hygiene and to obtain some prerequisite data of dermatophytes sensitivity, the dynamics of those inactivation by NTP plasma was monitored for various strains of Trichophyton iterdigitale, Trichophyton benhamiae, Trichophyton rubrum, and Microsporum canis. Three strains of each species on agar plates were exposed with plasma produced by a DC corona discharge in the point-to-ring arrangement in various time intervals. Although all strains were sufficiently sensitive to plasma action, significant differences were observed in their sensitivity and inactivation dynamics. These differences did not correlate with the species classification of individual strains, but could be assigned to four arbitrarily created types of strain response to NTP according to their sensitivity. These results indicate that the sensitivity to plasma is not an inherent property of the fungal species, but varies from strain to strain.
Keywords: DC corona discharge; Trichophyton; Microsporum; treatment of mycoses